Konflik Kewenangan Pemerintah Pusat dan Pemerintah DKI Jakarta dalam Penanganan Covid 19 di Indonesia - Muhammad Zubeir Sipahutar; Heri Kusmanto; Indra Kesuma Nasution (PERSPEKTIF, 2023)
This study aims to see how the conflict of authority in the relationship between the Central Government and the Government of DKI Jakarta is in overcoming the Covid-19 pandemic. This research is a qualitative research with a qualitative descriptive method and data collection techniques in the form of literature study. The results of this study indicate that the conflict of authority between the Central Government and the DKI Jakarta Government occurs due to the different orientations and interests of each government. Since detecting this virus in Jakarta in January 2020, the DKI Jakarta Government wants the issue of the Covid-19 pandemic to become a priority issue that must be responded to quickly because it involves the health of the local community. But on the other hand, the Central Government at that time was focusing on increasing economic growth by promoting the tourism and transportation sectors. This difference in views has an impact on the different policies taken so that they often overlap and make the handling of the Covid pandemic less than optimal. However, hierarchically, the Government of DKI Jakarta should follow the steps of the central government to avoid overlapping policies and avoid conflicts of authority.